Instant CMQT stabilization coupled UHPLC-MS/MS for the quantification of reduced and total forms of cysteine, homocysteine, and glutathione in blood plasma - Yongyin Zhou; Haizhu Tan; Yingtong Chen; Hongjun Luo; Hui Li; Wenhong Luo; Yingxiu Xiao; Zhexuan Lin (Analytica Chimica Acta, 2026)

Synergistic alkaline etching and nitrogen lattice occupation strategy enables gradient defluorinated cathode for high-performance Li/CFx batteries - Hongwei Cai; Xiaoxiao Pan; Cong Li; Hao Luo; Menghan Lin; Mingyi Shang; Jiqiong Lian; Yanan Fu; Hongjun Yue; Huixin Chen; Xiaolong Li; Yujin Tong; et al. (Chemical Engineering Journal, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

Experimental evaluation of the vortex-induced vibration suppression of catenary flexible riser with helical strakes - Hongjun Zhu; Bin Luo; Hongtao Hao; Yue Gao; Tongming Zhou (Ocean Engineering, 2026)

Decoupling and decomposition analysis of industrial carbon emissions, and projection of its future trends: A case study of Quanzhou, China - Yanxi Tang; Jing Xu; Muping Shen; Jiachang Zuo; Fengyi Yu; Yingmao Tang; Tingting Liu; Hongjun Jin; Yongjin Luo; Qingrong Qian; Qinghua Chen (Environment, Development and Sustainability, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Direct visual detection for methicillin-resistant Staphylococcus aureus in milk based on the RPA-Cas12a-LFS method - Yixiang Sun; Liren Zhang; Huimin Wu; Hongjun Chen; Huijie Hu; Chongyu Zhang; Xiaoqiang Li; Yuan Li; Yimai Wang; Liqiang Luo; Yizhi Song (Food Control, 2025)

Optimizing Lancang-Mekong hydropower portfolio effectively reduces greenhouse gas emissions - Xiaobo Yun; Qiuhong Tang; Jie Wang; Siao Sun; Hongjun Bao; Yadu Pokhrel; Lifeng Luo; Deliang Chen (Environmental Impact Assessment Review, 2025)

Chelation treatment for heavy metals in municipal solid waste incineration fly ash: 300-Day study on stability and environmental risk - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Qunhui Wang; Chuanfu Wu (Waste Management, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

Enhancing ozone catalytic decomposition through acid treatment of α-MnO2 for improved activity and humidity resistance - Shangchao Xiong; Kai Zhang; Zhenghao Xu; Hongjun Ou; Yuanyuan Zheng; Xi Li; Yue Peng; Xubiao Luo; Junhua Li (Journal of Environmental Sciences, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Unstable geomorphologic fabric impacted by excess magmas and propagating rifts in the central West Philippine Basin - Weidong Luo; Pin Yan; Gaowen He; Yufang Tan; Ruiying Ye; Hongjun Chen; Zhen Lin; Houjin Wang; Minghui Zuo; Changliang Chen; Junhui Yu; Yanlin Wang (Geomorphology, 2024)

Stabilization of heavy metals in municipal solid waste incineration fly ash using organic chelating agents: Insight into risk assessment and function mechanism - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Amirhomayoun Saffarzadeh; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2024)

Long-term Fertilizer Application Induces Changes in Carbon Storage and Distribution, and the Consequent Color of Black soil - Jichao Gao; Lichun Wang; Jiafa Luo; Hongjun Gao; Weiwen Qiu; Qiang Li; Xiuzhi Zhang; Ping Zhu; Chang Peng; Yunfei Jiao; Lingying Xu (Journal of Soil Science and Plant Nutrition, 2024)

Effects of childhood maltreatment and major depressive disorder on functional connectivity in hippocampal subregions - Huiqin Nie; Tong Yu; Yurong Zou; Yuhong Li; Juran Chen; Jinrou Xia; Qianyi Luo; Hongjun Peng (Brain Imaging and Behavior, 2024)

Dynamic characteristics of net anthropogenic phosphorus input to the upper Yangtze River Basin from 1989 to 2019: Focus on the phosphate ore rich area in China - Junlan Yang; Min Li; Lu Liu; Hongjun Zhao; Wenqing Luo; Yali Guo; Xiaonan Ji; Wei Hu (Journal of Environmental Management, 2023)

Solidification/stabilization and risk assessment of heavy metals in municipal solid waste incineration fly ash: A review - Ze Zhang; Chutong Zhao; Yi Rao; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2023)

SIRT3/GLUT4 signaling activation by metformin protect against cisplatin-induced ototoxicity in vitro - Peiyu Du; Tianyi Liu; Pan Luo; Hejie Li; Wei Tang; Shimin Zong; Hongjun Xiao (Archives of Toxicology, 2023)

Effects of shellfish culture on the community and mortality of zooplankton in a subtropical Bay - Bijian Pang; Hongjun Li; Mingmin Li; Xin Luo; Ying Chen; Tianshen Li; Wenlu Lan (Journal of Oceanology and Limnology, 2023)

Alkali-catalyzed hydrothermal oxidation treatment of triclosan in soil: Mechanism, degradation pathway and toxicity evaluation - Yushuang Chen; Rui Shi; Hongjun Luo; Rong Zhang; Yafei Hu; Haijiao Xie; Neng-min Zhu (Science of The Total Environment, 2023)

Aberrant brain connectivity is associated with childhood maltreatment in individuals with major depressive disorder - Qianyi Luo; Juran Chen; Yuhong Li; Zhiyao Wu; Xinyi Lin; Jiazheng Yao; Huiwen Yu; Huawang Wu; Hongjun Peng (Brain Imaging and Behavior, 2022)

Molecular characterization, expression, and apoptosis regulation of siva1 in protogynous hermaphrodite fish ricefield eel (Monopterus albus) - Zhi He; Faqiang Deng; Zhijun Ma; Qian Zhang; Jiayang He; Lijuan Ye; Hongjun Chen; Deying Yang; Liang He; Jie Luo; Taiming Yan (Fish Physiology and Biochemistry, 2021)

Update on recommendations for the diagnosis and treatment of SARS-CoV-2 infection in children - Hongjun Miao; Han Li; Yinying Yao; Mingfu Wu; Chao Lu; Jun Wang; Man Tian; Ying Li; Peiliang Luo; Jianhui Gu; Bin Yuan; Shouchuan Wang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
Since the outbreak of novel coronavirus infection pneumonia in Wuhan City, China, in late 2019, such cases have been gradually reported in other parts of China and abroad. Children have become susceptible to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of their immature immune function. As the outbreak has progressed, more cases of novel coronavirus infection/pneumonia in children have been reported. Compared with adults, the impact of SARS-CoV-2 infection in children is less severe, with a lower incidence and susceptibility in children, which results in fewer children being tested, thereby underestimating the actual number of infections. Therefore, strengthening the diagnosis of the disease is particularly important for children, and early and clear diagnosis can determine treatment strategies and reduce the harm caused by the disease to children. According to the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards ( trial version 7 ) issued by National Health Committee and the latest diagnosis and treatment strategies for novel coronavirus infection pneumonia in children, this review summarizes current strategies on diagnosis and treatment of SARS-CoV-2 infection in children.

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Physiological, genomic and transcriptomic comparison of two Brassica napus cultivars with contrasting cadmium tolerance - Shufeng Wang; Juanjuan Sun; Shengting Li; Kun Lu; Hongjun Meng; Zhongchun Xiao; Zhen Zhang; Jiana Li; Feng Luo; Nannan Li (Plant and Soil, 2019)

Oil mixing behavior after an oil spill: identification conflicts of different fingerprints - Shijie He; Hongjun Yu; Yongming Luo; Chuanyuan Wang; Xueshuang Li; Zhongping Li (Environmental Science and Pollution Research, 2018)

Using regression models to evaluate the formation of trihalomethanes and haloacetonitriles via chlorination of source water with low SUVA values in the Yangtze River Delta region, China - Huachang Hong; Qianyun Song; Asit Mazumder; Qian Luo; Jianrong Chen; Hongjun Lin; Haiying Yu; Liguo Shen; Yan Liang (Environmental Geochemistry and Health, 2016)